The youth experience gap explaining national differences in the school-to-work transition - Pastore, Francesco 1966-2022 (Springer Briefs in economics, 2015)
Some stylized facts -- The youth experience gap -- The mainstream approach to the causes of youth unemployment -- Weaknesses of the mainstream approach -- The interventionist approach -- A classification of school-to-work transition regimes -- Discussion and summary remarks